AGN feedback in galaxy group 3C 88: cavities, shock, and jet reorientation. Issue 3 (24th January 2019) - Liu, Wenhao; Sun, Ming; Nulsen, Paul; Clarke, Tracy; Sarazin, Craig; Forman, William; Gaspari, Massimo; Giacintucci, Simona; Lal, Dharam Vir; Edge, Tim
ABSTRACT: We present results from the deep Chandra observation (105 ks), together with new Giant Metrewave Radio Telescope and Very Large Array data of the AGN outburst in the radio-loud galaxy group 3C 88. The system shows a prominent X-ray cavity on the eastern side with a diameter of ∼50 kpc at ∼28 kpc from the nucleus. The total enthalpy of the cavity is 3.8 × 10 58 erg and the average power required to inflate the X-ray bubble is ∼ 2.0 × 10 43 erg s −1 . From surface brightness profiles, we detect a shock with a Mach number of M  = 1.4 ± 0.2, consistent with the value obtained from temperature jump. The shock energy is estimated to be 1.9 × 10 59 erg. The size and total enthalpy of the cavity in 3C 88 are the largest known in galaxy groups, as well as the shock energy. The eastern X-ray cavity is not aligned with the radio jet axis. This factor, combined with the radio morphology, strongly suggests jet reorientation in the last tens of million years. The bright rim and arm features surrounding the cavity show metallicity enhancement, suggesting they originated as high metallicity gas from the group centre, lifted by the rising X-ray bubbles. Our Chandra study of 3C 88 also reveals that galaxy groups with powerful radio AGN can have high cavity power, although deep X-ray observations are typically required to confirm the cavities in galaxy groups.